Transient Receptor Potential Vanilloid 1-Immunoreactive Innervation Increases in Fractured Rat Femur - Kawarai, Yuya (Yonsei University College of Medicine, 2014)
PURPOSE: Pain from vertebral or femoral neck fractures is a particularly important problem in clinical orthopaedics. Transient receptor potential vanilloid 1 (TRPV1) is a ligand-gated nonselective cation channel, and there are recent reports on an association between bone pain and TRPV1. However, an increase in TRPV1 activity has not been reported following femoral fracture. MATERIALS AND METHODS: We applied a neurotracer [Fluoro-gold (FG)] onto femur to detect dorsal root ganglia (DRGs) innervating the cortex of the femur in 30 Sprague Dawley rats. Seven days after application, a closed mid-diaphyseal fracture of the femur was performed. FG labeled TRPV1-immunoreactive (ir) DRGs innervating the femur were examined in nonfractured controls, and 3 days, 1 week, 2 weeks, and 4 weeks after fracture. We evaluated bone healing of the femur and compared the ratio of TRPV1-ir DRG neurons innervating the femur at the time points. RESULTS: Four weeks after fracture, complete bone union was observed. There was no significant difference in the ratio of FG labeled DRG neurons to total DRG neurons at each time point. The percentages of TRPV1-ir neurons in DRGs innervating the femur at 3 days and 1 week after fracture were significantly higher than those in control, 2 weeks, and 4 weeks after fracture (p<0.05). CONCLUSION: Fracture induced an increase of TRPV1-ir neurons in DRGs innervating the fractured femur within 3 days, and decreased during bone healing over 4 weeks. These findings show that TRPV1 may play a role in sensory sensation of bone fracture pain.